Strep‐Tag II and Monovalent Strep‐Tactin as Novel Handles in Single‐Molecule Cut‐and‐Paste. Issue 8 (18th July 2017) - Erlich, Katherine R.; Baumann, Fabian; Pippig, Diana A.; Gaub, Hermann E.
Abstract : Directed spatial assembly of single molecules on a surface presents an opportunity to precisely control the positioning, density, and geometry of molecules of interest within an ensemble. In contrast to bulk averaging, this enables detection and analysis of individual behavior within such a designed ensemble. The atomic force microscopy (AFM)‐based technique of single‐molecule cut‐and‐paste (SMC&P) facilitates the arrangement of a variety of biomolecules on a surface through different handling strategies. This technique requires cantilever‐ and surface‐handles that simultaneously adhere to a prerequisite rupture force hierarchy, and also do not cross‐interact with each other or the transported molecules. As the molecules of interest diversify, so too must the handling methods to accommodate their unique characteristics. Here, it is demonstrated that a previously developed monovalent variant of Strep ‐Tactin and its corresponding Strep ‐Tag II peptide ligand comprise a viable cantilever handling complex for SMC&P. Ultimately, this expansion to the SMC&P toolbox increases the system's versatility for new molecules of interest yet to be studied. Abstract : Arrangement and analysis of single molecules, in contrast to ensemble averaging, offers new avenues of investigation into molecular behavior. Single‐molecule cut‐and‐paste is a robust molecular organization technique that enables precise placement of individual molecules on a surface. The novel handling strategy described expands the versatility of this system, and promotes directed spatial arrangement of diverse molecules of interest.